MODEL KOMPETENSI DOSEN TERHADAP HASIL BELAJAR PADA MAHASISWA POLITEKNIK LP3I MEDAN - mayang murni; Muhammad Imaduddin (LPPM Politeknik LP3I Medan, 2019)
The purpose of National education is to create quality of human beings. In effort to improve and produce human resources, it is inseparable from the performance of all lecturers as the core of teaching and learning process. Lecturers are the main characters and key points in the whole process of education, especially in universities. The purpose of this study was to examine the influence of Lecturer Competency on Learning Outcome at Politeknik LP3I Medan. The four competencies as follows Pedagogical competence, personality competence, social competence and professional competence. This research is an Descriptive Quantitaive. The research in Politeknik LP3I Medan, wit 45 lecturers as respondents. Data collection in this research uses a questionnaire. Data analysis using multiple regressions analysis. The result of this research showed that the influence of personality competence and professional competence on learning outcome is significant, but influence of pedagogical competence and social competence on learning outcome is not significant. And then F test of Lecturer Competence Models on Learning Outcome at Politeknik LP3I Medan is not significant.